(untitled) (Economic and Political Thought, 2014)
The author analyses the role of international issues in the policy of Austria from the perspective of the election to the National Council that took place on 29 September 2013. The article presents the analysis of particular parties’ approach to those issues, including the Social Democratic Party of Austria (Sozialdemokratische Partei Österreichs, SPÖ), the Austrian People’s Party (Österreichische Volkspartei, ÖVP), the Freedom Party of Austria (Freiheitliche Partei Österreichs, FPÖ), The Greens – The Green Alternative (Die Grünen – Die Grüne Alternative, GRÜNE), Team Stronach for Austria (Team Stronach für Österreich, TS), NEOS – the New Austria and Liberal Forum (NEOS – Das Neue Österreich), and the Alliance for the Future of Austria (Bündnis Zukunft Österreich, BZÖ). The article describes the role of international organisations in the contemporary policy of that country. Attention is drawn to the debate of that time on the participation of Austrian troops in the UN operations. The role of history in the contemporary discourse on the Austrian foreign policy is also an important element. The issues connected with the attitude towards the Nazi past of the country are worth mentioning here in particular.